Analisis Kesalahan Pelafalan Bahasa Korea oleh Orang Indonesia Perubahan Konsonan Letup menjadi Konsonan Sengau - , MELIZZA FONASTIA, Achmad Rio Dessiar, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper entitled \"Analysis of Korean Language Pronunciation Errors of Indonesian People: Plosive Consonants Changed be Nasal Consonantsâ. This study is the describes of field research on the pronunciation of Korean language which was conducted on the Korean language students on Vocational School UGM Batch 2012. This study explains and discusses the common pronunciation errors that are made by the Korean language students on Vocational School UGM Batch 2012. The data were obtained through interview method and analysis of existing literature studies. The data analysis reveals that the Korean language students on Vocational School UGM Batch 2012 are likely to mispronounce the Korean words. There are three rules of Korean language pronunciation which were examined within this study: there are bilabial plosives consonants changed be nasal consonants, alveolar plosives consonants changed be nasal consonants and velar plosives consonants changed be nasal consonants. Among the 3 rules of Korean language pronunciation, Korean language students make the most mistakes while pronouncing the words of velar consonant that met with nasal consonants